An Interesting Case of Gradenigo Syndrome. Issue 1 (2nd January 2019) - Suzich, Kristen L.; Adelson, Sarah; Choi, Catherine S.
ABSTRACT: Gradenigo syndrome is a rare complication of acute otitis media infections, and early diagnosis and treatment of the condition are imperative. In this report, we present a case of a 22-month-old girl who developed acute, acquired esotropia associated with recurrent episodes of otitis media, which resolved after antibiotic treatment. To our knowledge, our patient is one of the youngest children reported in the literature to present with presumed Gradenigo syndrome and the only case of recurrent episodes of acquired esotropia and concurrent otitis media within the short time span of 1 month. We hope to add new information to the existing literature and to aid in the understanding of the pathophysiology and management of this condition.